2015
DOI: 10.1002/mds.26484
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Exercise to Improve Mood, Cognition, and Sleep in Parkinson's Disease

Abstract: In addition to the classic motor symptoms, Parkinson’s disease (PD) is associated with a variety of non-motor symptoms that significantly reduce quality of life, even in the early stages of the disease. There is an urgent need to develop evidence-based treatments for these symptoms, which include mood disturbances, cognitive dysfunction, and sleep disruption. We focus here on exercise interventions, which have been used to improve mood, cognition, and sleep in healthy older adults and clinical populations, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 238 publications
3
64
0
6
Order By: Relevance
“…The BAI motor factor mediated the effect of PD on anxiety. Though PD is associated with greater anxiety disturbances than seen in the general population [1, 24], on the widely-used BAI the effect of PD was significantly influenced by their scores on motor items. BAI scores remained significantly higher for PD than NC even when accounting for motor items, however, indicating that the BAI does measure anxiety (apart from motor disturbances) in PD relative to a non-PD population.…”
Section: Discussionmentioning
confidence: 99%
“…The BAI motor factor mediated the effect of PD on anxiety. Though PD is associated with greater anxiety disturbances than seen in the general population [1, 24], on the widely-used BAI the effect of PD was significantly influenced by their scores on motor items. BAI scores remained significantly higher for PD than NC even when accounting for motor items, however, indicating that the BAI does measure anxiety (apart from motor disturbances) in PD relative to a non-PD population.…”
Section: Discussionmentioning
confidence: 99%
“…A review based on seven studies concluded that physical exercise can improve motor symptoms and several NMS in PD 193 , possibly by improving perfusion, or by promoting growth hormone release or angiogenesis. In one relatively large study, 51 PD patients without dementia were randomly assigned to a progressive strengthening exercise training programme or to a simpler programme focusing on stretching, balance, breathing and non-progressive strengthening, administered twice a week for 24 months 194 .…”
Section: Managementmentioning
confidence: 99%
“…Nevertheless, a beneficial effect of exercise on motor symptoms of PD as well as a general health benefit (physical fitness) seems likely from these studies. A beneficial effect on non-motor symptoms in PD is also conceivable, but not yet proven 2. To strengthen the evidence on symptomatic benefits, we need methodologically sound randomised controlled trials (RCTs) with large sample sizes, clinically relevant outcomes for both motor and non-motor signs, long-term interventions and prolonged follow-up 3.…”
Section: Introductionmentioning
confidence: 99%